A face oculta do caboclo de Curitibanos, Santa Catarina, perdas e rupturas em sua peregrinação da economia de subsistência para o trabalho precarizado - Lemos, Silse Teixeira de Freitas (2006)
The thesis presents reflection and critical analyses of the construction of the identity of the caboclo and its transformation into worker in the wood saw mills in Curitibanos, Santa Catarina. It is situated in the comprehension of the contemporaneous reality, a fertile field for the Social Service. Accomplished by bibliographic and quantity research anchored in oral history, it delves into the Brazilian colonization process of the first occupations until the conquer of the meridian Brazil, scenario where man will build up its identity , with the incidence of environmental, social, economic, political and cultural factors. Curitibanos is approached in its constitution that involves the geographic space, historical facts, the man, the colonialist politics and in the authoritarianism. The Contestado Campaign is presented as remarkable in the lives of the inhabitants of the region for providing the attributions of the characteristics in its identity. The social relations are analyzed in the perspective of totality and singularity, in the historical movement that culminates in the contemporaneousness, situates in the concretion of the way of life of the caboclo. The use of the land for provision of survival, the organization of the labor process, the repercussions in the existence of the worker and its insertion as salary worker in the saw mills serve to comprehend the attributed identity. The political and social relations show the recrudescence of the authoritarianism and point to the poor economy. With the end of the extraction of the native wood, contingents of workers migrate to the urban suburbs submitted to the precariousness of the work and to the unemployment. They convert to users of social politics, - whose constitution profile is presented in the punctual mode in the course of affirmation of the society and of the modern state - , one of the spaces of actuation of the social service professionals